Analysis of the change trend of the structure of health technicians in Tianjin hospitals - Guo, Jinlin; He, Ning (Transactions on Economics, Business and Management Research, 2024)
Objective: To analyze the overall development trend and internal structure changes of health technicians in Tianjin hospitals from 2011 to 2022, and to provide suggestions for promoting the better development of health technicians in Tianjin hospitals. Methods: Descriptive analysis and structural change analysis were used to study the development of health technicians. Results: In terms of overall development, the number of health technicians in Tianjin hospitals increased year by year, reaching 85,215 in 2022, with a growth rate of 59.15%. From the perspective of structural change, the structural change value of practicing (assistant) physicians and registered nurses showed a positive change, and the overall structural change showed a trend of first decreasing and then increasing, reaching the highest value of 4.41% in 2021 and the smallest structural change of only 0.38% in 2018. In terms of the contribution rate of structural change, the structural change rate of registered nurses among the health technicians in Tianjin hospitals was relatively active, with an average of 26.88%. Conclusion: The total number of health technicians in Tianjin hospitals is insufficient, and it is necessary to expand the talent pool. The structure of registered nurses is actively changing, and it is necessary to consider controlling the quality of practitioners from the source; The structure of pharmacists and technicians is unstable, and attention should be paid to the professional development of physicians.